On beauty, usefulness, and holiness: attitudes towards languages in the Habad community. Issue 2 (7th February 2017) - Tannenbaum, Michal; Cohen, Hagit
ABSTRACT: This paper studies one ultra-Orthodox group – Habad community, exploring its members' attitudes towards four languages: Hebrew, Loshen Koydesh (LK), English, and Yiddish, and focusing on usage, affection for the language, ascribed importance, and holiness. Research questions were: (1) What are the attitudes of Habad members towards these languages? (2) Are there individual differences according to gender and/or age in the attitudes towards these languages within the group? One hundred forty-eight questionnaires were distributed to members of the community, and semi-structured interviews were conducted with 20 participants. Attitudes towards the four languages revealed significant differences, showing, by and large, a preference for Hebrew, LK, and English over Yiddish in all dimensions, yet yielding a range of specific gender and age differences reflecting the sociocultural milieu's influence on the development of these perceptions. Habad's unique features came forth in its members' linguistic choices and attitudes, providing further evidence of language as both reflecting and directing issues of identity, belongingness, ideology, and intergroup relations.